WEB APPLICATION FOR ONLINE TRACK OCCUPATION DIAGRAM MANAGEMENT IN A RAILWAY STATION - Jan Žampach; Michael Bažant (Perner’s Contacts, 2013)
The work deals with the problem of track occupation diagram management for larger passenger railway stations. It summarizes the current techniques of diagrams creation, its usefulness for railway dispatchers and other managers. The practical aim of this work is to design and implement a web application that would partially allow to automate the process of diagram creation and to provide interactive tool for operational traffic control with an option to make dynamic changes.